Expanding Ricci solitons asymptotic to cones - Chodosh, Otis (Calculus of variations and partial differential equations, 2014)
We show that an expanding gradient Ricci soliton which is asymptotic to a cone at infinity in a certain sense must be rotationally symmetric.